Boundary Functionals for the Difference of Nonordinary Renewal Processes with Discrete Time - Yezhov, I. I.; Kadankov, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For the difference of nonordinary renewal processes, we find the distribution of the main boundary functionals. For the queuing system D η δ |D ξ κ |1, we determine the distribution of the number of calls in transient and stationary modes.